Effectiveness of Blended Learning Model in Microprocessor Course with Google Classroom - Taali; Abdul Habib Arrasyidi Desky; Arief Juneirul Pratama; Herlin Setiawan (Jurnal Penelitian Pendidikan IPA, 2024)
Low student learning outcomes in microprocessor courses. This can be created if students are not able to condition themselves and take the learning process seriously. The importance of independent learning (self-regulated) of students, then an innovative learning process is also needed that can support student skills. One of the learning processes that can support the improvement of student learning outcomes is blended learning. The purpose of this study is to examine how Google Classroom supports the blended learning approach, which enhances student learning outcomes. This kind of study is known as quasi-experimental. Design of Pretest-Posttest. The research was conducted at the Electrical Engineering Education Study Program at Padang State University with a total of 32 experimental class students and 31 control class students. The research instruments used were observation sheets of the application of the blended learning model, student learning outcomes questionnaire. Data analysis was carried out with technical mean percentage, n-gain, and independent t-test. The results showed that the application of blended learning was effective on student learning outcomes at 5% sig tarag which was seen from the value of tcount > ttable, namely 4.75 > 1.67. There was an increase in student learning outcomes with a posttest value of 80.25. Based on the data that has been analyzed, it can be concluded that the application of blended learning assisted by Google Classroom is effective in supporting to improve student learning outcomes